Manual of Fertility Enhancing Hysteroscopy (Springer Singapore, 2018)
This book is an illustrated yet comprehensive compilation by experts in the field of fertility enhancing endoscopic surgery and assisted reproduction. This book catalogues full spectrum of diagnostic and operative hysteroscopy in the infertile population. The authors describe different techniques in various clinical conditions and review the recent evidence based literature supporting them. All procedures are explained in clear and precise text supplemented with high quality color pictures.